Combination of a large cation and coordinating additive improves carrier transport properties in quasi-2D perovskite solar cells. Issue 14 (25th March 2021) - Sahayaraj, Sylvester; Radicchi, Eros; Ziółek, Marcin; Ścigaj, Mateusz; Tamulewicz-Szwajkowska, Magdalena; Serafińczuk, Jarosław; De Angelis, Filippo; Wojciechowski, Konrad
Abstract : A Lewis base additive is used to stimulate vertical orientation and even the distribution of low dimensional perovskite crystallites, improving photovoltaic performance. Abstract : Two-dimensional perovskite materials have attracted considerable attention from the photovoltaic community, primarily due to their superior environmental stability. It mainly originates from the presence of bulky organic spacer cations that enhance structural stability and moisture resistance. This feature comes with a price, as large cations reduce the anisotropic character of charge transport in 2D-perovskite films, making the cells less efficient than their 3D counterparts. The control of grain orientation in the out-of-plane direction is crucial for enabling efficient device operation. Here, a coordinating additive, thiosemicarbazide (TSC), is reported as an effective templating agent for highly oriented growth (out-of-plane orientation) of low dimensional perovskite crystallites. The effect of TSC is compared to that of ammonium thiocyanate (NH4 SCN), which has been reported to stimulate vertical grain orientation. Furthermore, by introducing 4-fluorophenylethylammonium iodide (4F-PEAI) as an organic spacer into the perovskite composition containing TSC, significantly enhanced photovoltaic performance was obtained, reaching a power conversion efficiency of 14.1%. Spectroscopic characterization methods were employed to identify different low dimensional phases present in the perovskite layer, and their distribution across the film. The even spread of low n (2D-like) and bulk (3D-like) phases observed for the combination of TSC and 4F-PEAI is assigned to the improved charge transport characteristics. Furthermore, the new precursor formulation (containing TSC and 4F-PEAI) yields devices with significantly enhanced long-term reliability, which was tested under different aging conditions (elevated temperature and maximum power point tracking).